LTBK-04. LATE BREAKING ABSTRACT: MEK162 (binimetinib) in children with progressive or recurrent low-grade glioma: a multi-institutional phase II and target validation study. (13th June 2022) - Robison, Nathan; Pauly, Jasmine; Malvar, Jemily; Gardner, Sharon; Allen, Jeffrey; Margol, Ashley; MacDonald, Tobey; Bendel, Anne; Kilburn, Lindsay; Cluster, Andrew; Bowers, Daniel; Dorris, Kathleen; et al.
Abstract: BACKGROUND: RAS/RAF/MEK/ERK pathway activation is the primary driver for most pediatric low-grade gliomas (pLGG). MEK162 (binimetinib) is an orally bioavailable MEK1/2 inhibitor with superior brain penetration in a preclinical model. The primary objective of this multi-institutional phase II and target validation study was to assess stratum-specific efficacy of binimetinib in progressive pLGG. METHODS: Eligible children aged 1-18 years with previously treated radiographically progressive pLGG were enrolled and treated with binimetinib, starting dose 32mg/m 2 /dose twice daily. Stratum 1 included patients with pLGG with documented BRAF fusion; stratum 2, neurofibromatosis 1 (NF1)-associated pLGG; stratum 3, sporadic pLGG without documented BRAF fusion; and stratum 4, patients undergoing planned tumor biopsy who began binimetinib preoperatively. Partial and minor responses (PR and MR) were defined as ≥50% and ≥25% decrease in maximal two-dimensional measurements. RESULTS: Of 86 patients enrolled, 85 were evaluable for response. Of these, 48 (56%) showed a radiographic response (30 PR and 18 MR) in the first year of treatment. Response rate for stratum 1 (n=28) was 50% (12 PR and 2 MR); 12 (43%) had stable disease (SD) and 2 (7%) progressive disease (PD). Stratum 2 (n=21) response rate was 43% (5 PR, 4 MR), with 12 (57%) SD and no PD. Stratum 3 (n=29) response rate was 69% (10 PR, 10 MR), 4 (14%) SD and 5 (17%) PD. Stratum 4 (n=7) include 3 PR, 2 MR, 2 SD. Nineteen (22%) discontinued treatment for toxicity (most commonly dermatologic), and an additional 42 (49%) required dose reduction. Median dose at the time of PR/MR was 28mg/m 2 ; responses were seen at doses as low 16mg/m 2 . CONCLUSION: Binimetinib is highly effective in the treatment of both NF1-associated and sporadic pLGG, with or without documented BRAF fusion. Modified dosing strategies to improve tolerability may be considered in future trials.